Economic evaluation of antibody-drug conjugates (ADCs) in patients with breast cancer: systematic review - Mohammad Ali Rezaei; Hamid Pourasghari; Fereshte Karimi; Soheila Rajaie; Amirreza Shahmohammady; Masoud Behzadifar; Amir Hossein Dehqan; Samad Azari (European Journal of Clinical Pharmacology, 2025)

Proliferating and migrating effects of regenerating sea anemone Aulactinia stella cells-derived exosomes on human skin fibroblasts - Nazanin Jafari; Alireza Afshar; Afshin Zare; Aria Salehpour; Alireza Hashemi; Fatemeh Zendehboudi; Zohreh Farrar; Mahdi Mahdipour; Arezoo Khoradmehr; Firouzeh Jahanfar; Nadiar M. Mussin; Asset A. Kaliyev; et al. (Natural Product Research, 2025)

The cost-effectiveness analysis of semaglutide for the treatment of adult and adolescent patients with overweight and obesity: a systematic review - Ali Sarabi Asiabar; Mohammad Ali Rezaei; Dariush Jafarzadeh; Soheila Rajaei; Pezhman Atefimanesh; Samira Soleimanpour; Mohammad Hossein Kafaei Meher; Samad Azari (European Journal of Clinical Pharmacology, 2024)

Characteristics of Microplastics in a Hospital Wastewater Treatment Plant Effluent and Hazard Risk Assessment - Hossein Kamani; Mehdi Ghayebzadeh; Ali Azari; Fatemeh Ganji (Environmental Processes, 2024)

Influence of chitosan coating on the physicochemical and antioxidant properties of phycocyanin-loaded nanoliposomes - Abdolkhalil Azari; Seyyed Hossein Hosseini Ghaboos; Vahid Erfani Moghadam; Seid Mahdi Jafari (Algal Research, 2023)

Supplier selection in the industry 4.0 era by using a fuzzy cognitive map and hesitant fuzzy linguistic VIKOR methodology - Asana Hosseini Dolatabad; Jalil Heidary Dahooie; Jurgita Antucheviciene; Mostafa Azari; Seyed Hossein Razavi Hajiagha (Environmental Science and Pollution Research, 2023)

Decellularization of kidney tissue: comparison of sodium lauryl ether sulfate and sodium dodecyl sulfate for allotransplantation in rat - Mohammad Amin Keshvari; Alireza Afshar; Sajad Daneshi; Arezoo Khoradmehr; Mandana Baghban; Mahdi Muhaddesi; Pouya Behrouzi; Mohammad Reza Miri; Hossein Azari; Iraj Nabipour; Reza Shirazi; Mehdi Mahmudpour; et al. (Cell and Tissue Research, 2021)

Integrated preprocessing techniques with linear stochastic approaches in groundwater level forecasting - Arash Azari; Mohammad Zeynoddin; Isa Ebtehaj; Ahmed M. A. Sattar; Bahram Gharabaghi; Hossein Bonakdari (Acta Geophysica, 2021)

Development of a new method for sampling and monitoring oncology staff exposed to cyclophosphamide drug - Davood Panahi; Mansour Azari; Mohammad Esmaeil Akbari; Rezvan Zendehdel; Hamid Reza Mirzaei; Hossein hatami; Yadollah Mehrabi (Environmental Monitoring and Assessment, 2016)

Enhanced chromium (VI) removal using activated carbon modified by zero valent iron and silver bimetallic nanoparticles - Babak Kakavandi; Roshanak Rezaei Kalantary; Mahdi Farzadkia; Amir Hossein Mahvi; Ali Esrafili; Ali Azari; Ahmad Reza Yari; Allah Bakhsh Javid (Journal of Environmental Health Science and Engineering, 2014)
Recently, adsorption process has been introduced as a favorable and effective technique for the removal of metal ions from aqueous solutions. In the present study, bimetallic nanoparticles consisting of zero valent iron and silver were loaded on the activated carbon powder for the preparation of a new adsorbent (PAC-Fe o /Ag). The above adsorbent was characterized by using XRD, SEM and TEM techniqes. Experimental data were exploited for kinetic, equilibrium and thermodynamic evaluations related to the adsorption processes. The Cr(VI) adsorption process was found to be favorable at pH 3 and it reached equilibrium state within 60 min. The stirring rate did not have a significant effect on the adsorption efficiency. Furthermore, the monolayer adsorption capacity of Cr(VI) based on the Langmuir model was measured to be 100 mg/g. The experimental equilibrium data were fitted to the Freundlich adsorption and pseudo second-order models. According to the thermodynamic study, the adsorption process was spontaneous and endothermic in nature, indicating the adsorption capacity increases with increasing the temperature. The results also revealed that the synthesized composite can be potentially applied as a magnetic adsorbent to remove Cr(VI) contaminants from aqueous solutions.